Quality criteria for multi-domain studies in the indoor environment: Critical review towards research guidelines and recommendations. (December 2022) - Chinazzo, Giorgia; Andersen, Rune Korsholm; Azar, Elie; Barthelmes, Verena M.; Becchio, Cristina; Belussi, Lorenzo; Berger, Christiane; Carlucci, Salvatore; Corgnati, Stefano Paolo; Crosby, Sarah; Danza, Ludovico; de Castro, Luiza; et al.
Abstract: The perception, physiology, behavior, and performance of building occupants are influenced by multi-domain exposures: the simultaneous presence of multiple environmental stimuli, i.e., visual, thermal, acoustic, and air quality. Despite being extensive, the literature on multi-domain exposures presents heterogeneous methodological approaches and inconsistent study reporting, which hinder direct comparison between studies and meta-analyses. Therefore, in addition to carrying out more multi-domain studies, such investigations need to be designed, conducted, and documented in a systematic and transparent way. With the goal to facilitate and support future multi-domain studies and their meta-analyses, this work provides (1) a range of criteria for multi-domain study design and reporting (i.e., defined as quality criteria), and (2) a critical review of the multi-domain literature based on the described criteria, which can serve as guidelines and recommendations for future studies on the topic. The identified quality criteria encompass study set-up, study deployment and analysis, and study outcome, stressing the importance of adopting a consistent terminology and result reporting style. The developed critical review highlights several shortcomings in the design, deployment, and documentation of multi-domain studies, emphasizing the need for quality improvements of future multi-domain research. The ultimate goal of this work is to consolidate our knowledge on multi-domain exposures for its integration into regulatory resources and guidelines, which are currently dominated by single-domain knowledge.